Linking proactive personality to successful aging at work: a moderated mediation model - Zhuo, Lijun; Wu, Qian; Cong, Yating; Bao, Xinyu (Frontiers in Psychology, 2025)
Using lifespan development theory, we explored how proactive personality influences successful aging at work among older physicians in public hospitals. Job crafting as a mediator and perceived organizational support as a moderator in this relationship. A moderated mediation model was developed and tested on a sample of 472 older physicians in 13 public hospitals in China. Hierarchical regression analysis was employed to test the study hypotheses. Regression analysis revealed a positive association between proactive personality and successful aging at work, with job crafting serving as a positive mediator in this relationship. Perceived organizational support moderated the indirect effect of proactive personality on successful aging at work via job crafting. Older physicians perceive higher level of organization support, the indirect effect was stronger. Our study makes important contributions to the extant literature by indicating whether, how, and when proactive personality has an effect on successful aging at work of older physicians. By the personality traits of older physicians, organizations should offer targeted guidance and training to help them adjust their roles and facilitate their adaptation to changes in the workplace.